THE EFFECTS OF SALT ON BREAD: TECHNOLOGICAL CONSIDERATIONS FOR REDUCED SALT LEVELS - Helen Tuhumury (AGRICA, 2011)
Salt is a dietary mineral composed primarily of sodium chloride. These two components of salt are an essential nutrient for humans with important functions in regulating the extracellular fluid volume and the active transport of molecules across cell membranes. However, having too much salt in the diet increases the risk of health problems. High sodium intake is positively correlated with the level of blood pressure. Therefore, it is necessary to consume food with reduced salt content. Salt has been used as a food preservative that kills or limits of foodborne pathogens and spoilage organism by decreasing water activity. Salt also has functions in foods by adding flavour and masking bitter tastes, controlling the growth of yeast and strengthening the dough network and gas retention of the dough. Reducing salt content in processed food especially for bread-based products is one of the greatest ongoing challenges facing food manufactures. It also has been difficult to reduce or remove salt or sodium chloride from bread since salt is one of the four essential ingredients in bread. Reducing salt level from 1.2% does not significantly affect dough rheological properties and bread-making quality. However, the omission of salt entirely leads to a significant reduction in the dough, bread quality and its palatability.